Pesantren sebagai Pusat Transformasi integritas: Upaya Preventif terhadap Budaya Korupsi di Kalangan Generasi Muda - Nur Syafaat, Imron; Muttaqin, Ahmad Ihwanul; Shohib , Moch (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2024)
Pesantren serve as pivotal institutions in cultivating integrity and addressing the pervasive issue of corruption among Indonesia's younger generation. Corruption, which undermines social, economic, and moral structures, has become a critical concern, particularly within the education sector. This study explores how value-based education in pesantren can serve as an effective strategy to instill anti-corruption character traits among students. By integrating moral principles such as honesty, trustworthiness, and justice into daily practices, pesantren aim to transform these values from theoretical concepts into actionable behaviors. Using a qualitative case study approach, the research was conducted at Madrasah Aliyah Darul Ulum Al Amin, involving seven informants, including kyai, teachers, and students. Data were gathered through in-depth interviews, participant observations, and documentation, then analyzed using content analysis techniques. The findings highlight the significant role of religious values, exemplified through educators' consistency and cooperative learning activities, in fostering moral character. Kyai and ustadz emerged as role models, demonstrating the values they teach, which deeply influenced students’ behaviors and perspectives.The study underscores the importance of a holistic and integrated approach to value education, combining religious teachings, exemplary leadership, and experiential learning. This combination proved effective in embedding anti-corruption principles into students’ daily lives, preparing them to navigate moral dilemmas with integrity. These findings provide a framework for educational institutions aiming to develop ethically grounded future generations while addressing societal challenges such as corruption.